2020
DOI: 10.1021/acsaem.0c01243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photonic Curing Processing Conditions on MAPbI3 Film Properties and Solar Cell Performance

Abstract: Thermal annealing is the most used postdeposition materials processing method in laboratory research, but due to its slow speed and high energy cost, it is not compatible with the upscaling and commercialization of perovskite solar cell (PSC) manufacturing. Here, we adapt photonic curing (PC), which uses millisecond light pulses to deliver energy to the sample, to replace thermal annealing for crystallization of methylammonium lead iodide (MAPbI 3 ) films and rapid fabrication of PSCs. We study how PC conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…For large-area manufacturing, two issues are of particular concern: uniformity and web speed. Xu et al (2020) have already demonstrated ∼5% variation across 5 inches in the cross-web direction for PC MAPbI 3 films. Down-web uniformity using photonic curing for processing is a concern because the light pulses are discrete while the substrate is conveyed at high speed underneath the lamp.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…For large-area manufacturing, two issues are of particular concern: uniformity and web speed. Xu et al (2020) have already demonstrated ∼5% variation across 5 inches in the cross-web direction for PC MAPbI 3 films. Down-web uniformity using photonic curing for processing is a concern because the light pulses are discrete while the substrate is conveyed at high speed underneath the lamp.…”
Section: Discussionmentioning
confidence: 90%
“…Photonic -30 pulses) to the sample at repetition rates ranging from 0.1 to 1 Hz and a lamp voltage of 500 or 700 V. All PC MAPbI 3 samples were processed using a single pulse with a lamp voltage of 300 V and a pulse length of 20 ms. This PC processing condition for MAPbI 3 was adapted from our previous work on 1 mm glass (Xu et al, 2020), with the lamp voltage reduced for the thinner WG substrates. To compare the PC MAPbI 3 conversion on top of TA or PC NiO x HTL, we first conducted XRD to confirm the crystallinity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intense pulsed light is a non-contact rapid heating method which can offer fast millisecond pulses of broad spectrum light (190-1100 nm) from xenon lamps [74]. Xenon lamps are used to provide high-energy pulse light to 150 J/cm 2 for perovskite annealing, and can achieve thin film crystallization at the millisecond scale [54,70,[75][76][77][78][79]. Druffel et al successfully employed intense pulsed light generated by a xenon lamp to sintering of MAPbI 3 on a mesoporous TiO 2 substrate for first time [76].…”
Section: Electromagnetic Wave Annealingmentioning
confidence: 99%